The goal of this ceremony / Priestly Lanting Layang ... [et al.] - Layang, Priestley Lanting; Abang Shamshudin, Dayang Nurul Amieyda; Herman, Nurul Izzah; Standard, Stephanie Sonia; Mokhtar, Muhammad Adib Azfar (Perpustakaan Tun Abdul Razak, 2023)
In order to get an education degree, you have to study until late at night and get up early. It could be hard, upsetting, and take a lot of time. Add up all the late nights you spent studying for a test or rushing to get to class on time. We know it was sometimes hard, but now is the time to look back and see how much it was worth. Convocation is the time to be proud of what you've done and give yourself a pat on the back.